Discrimination against Women in Hiring - Adam Osman; Jamin D. Speer; Andrew Weaver (Institute of Labor Economics (IZA), 2023)
We study discrimination in hiring and its associated outcomes for the discriminators using a unique survey of Egyptian businesses. Discrimination against women is widespread and overt: about half (51%) of establishments directly admit that they prefer to hire men. The share varies widely across industries, from 60% in retail to only 16% in IT. Using a list randomization technique, we can rule out that discrimination against women is heavily stigmatized in Egypt, meaning that establishments are willing to admit it openly. We then provide novel suggestive evidence showing that discriminating against women is associated the employment of lower-quality workers. We also provide guidance on the use of the list randomization technique and how to interpret it in settings with limited stigma.
Keywords: J16; J71; C83; O12; 330; discrimination; list randomization; Egypt